Audit Forensic on Patra Niaga - Juninetenth Keeply F Sitanggang; Nur Aziza; Fricillia Vina Cindy Tioria Sitorus; Rimba Simanjuntak; Rahima Br Purba (International Journal of Management, Economic and Accounting, 2025)
Forensic audit is an investigative approach integrating accounting, auditing, and legal expertise to uncover fraudulent practices within business entities and public sectors. This study aims to evaluate the effectiveness of forensic audits in identifying and exposing manipulation in the subsidised fuel distribution system conducted by PT PatraNiaga, a subsidiary of PT Pertamina (Persero). Through literature review and case analysis methods, the study finds that forensic auditing successfully revealed various fraudulent schemes, including nozzle data fabrication, double recording in distribution systems, and concealment of fuel logistics flow. Key audit techniques such as document tracing, ERP logistics audit trails, investigative interviews, and data mining played a crucial role in uncovering these irregularities. The audit findings demonstrate that structural weaknesses in distribution systems, poor internal controls, and the lack of integrated digital monitoring systems significantly contributed to the occurrence of fraud. Recommendations include strengthening investigative audit units, revising standard operating procedures (SOPs) for fuel distribution, reactivating whistleblower systems, and integrating real-time monitoring technologies. This study affirms that forensic audit serves not only as a detection tool but also as a systemic reform catalyst in the governance of national energy distribution.